Postoperative Pain Assessment after Pediatric Otolaryngologic Surgery. Issue 11 (25th July 2013) - Schnelle, Ariane; Volk, Gerd Fabian; Finkensieper, Mira; Meissner, Winfried; Guntinas‐Lichius, Orlando
Abstract Objectives To describe postoperative pain within the first 24 hours after pediatric otolaryngologic surgery and to identify factors influencing postoperative pain. Methods One‐hundred and thirty four children were included in a prospective cohort single center study. Outcome and process parameters were analyzed using the questionnaires of the German‐wide project Quality Improvement in Postoperative Pain Management in Infants (QUIPSI). Results Maximal pain within the first 24 hours after typical otolaryngologic surgery reached average numeric rating scale values of 4.00 ± 3.49. About one fifth demanded more pain medications. Inpatient surgery, longer surgery, and major surgery were associated with more maximal pain. Analysis of analgesic use on the ward indicated insufficient utilization of these drugs, especially when piritramide was used (beta = 3.597, P = 0.039). When ibuprofen was used on the ward, this was significantly associated with the desire for more pain medication (odds ratio [OR]: 0.274, confidence interval [CI]: 0.103‐0.725, P = 0.009). Children with American Society of Anesthesiologists status 2 were more fatigued after surgery than status 1 children (OR: 0.296, CI: 0.100–0.874, P = 0.028). Nausea was more common when ibuprofen was used on the ward for pain treatment (OR: 0.195, CI: 0.049–0.777, P = 0.020). Conclusions QUIPSI is an easy tool to evaluate the quality of postoperative pain management following pediatric otolaryngologic surgery in children older than 3 years, especially in children older than 9 years. The maximal pain values within the first 24 hours are significant, so that pain therapy is required. It seems that both nonopioids and opioids are underdosed.